2004
DOI: 10.1063/1.1647686
|View full text |Cite
|
Sign up to set email alerts
|

La 0.95 Sr 0.05 CoO 3 : An efficient room-temperature thermoelectric oxide

Abstract: We present measurements of electrical resistivity, thermal conductivity and thermopower of polycrystalline Sr-doped LaCoO3 with composition La0.95Sr0.05CoO3. Our data show that the investigated compound exhibits a very respectable room temperature thermoelectric figure of merit value of 0.18. Our results not only show that oxides are promising candidates for thermoelectric cooling applications, but also point towards the need for careful theoretical calculations that will serve as a guide in producing the next… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
120
6

Year Published

2005
2005
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 184 publications
(131 citation statements)
references
References 21 publications
5
120
6
Order By: Relevance
“…These values are somewhat higher than the power factor reported in Ref. [28] for La 0.95 Sr 0.05 CoO 3 but are much smaller than the value reported by Androulakis et al [27], who found an unusually large Seebeck coefficient (700 µV K -1 at 300 K).…”
Section: Magnetic Transport And/or Thermoelectrical Propertiescontrasting
confidence: 52%
See 1 more Smart Citation
“…These values are somewhat higher than the power factor reported in Ref. [28] for La 0.95 Sr 0.05 CoO 3 but are much smaller than the value reported by Androulakis et al [27], who found an unusually large Seebeck coefficient (700 µV K -1 at 300 K).…”
Section: Magnetic Transport And/or Thermoelectrical Propertiescontrasting
confidence: 52%
“…Both the bismuth cobaltite and the cobalt perovskites are known to display thermoelectrical properties [24][25][26][27][28]. In Fig.…”
Section: Magnetic Transport And/or Thermoelectrical Propertiesmentioning
confidence: 99%
“…Th e strong electronic correlation eff ect in this material has been attributed to the unusually large Seebeck coeffi cient [77]. Many researchers subsequently started to explore high-performance oxides for TE applications, and some promising TE oxides have emerged, including Zn 1-x Al x O (n-type, ZT ≈ 0.30 at 1273 K) [78], La 1-x Sr x CoO 3 (p-type, ZT ≈ 0.18 at room temperature) [79], and La 1-x Y x CuO 4 (p-type, ZT ≈ 0.17 at 330 K) [80].…”
Section: Other Systemsmentioning
confidence: 99%
“…Perovskite Co oxides also show very rich physics such as spin-state transition [4,5], ferromagnetism [6], and thermoelectricity [7]. The ferromagnetism in the perovskite Co oxide La 1−x Sr x CoO 3 has been explained in terms of the double-exchange interaction between Co 3+ and Co 4+ in the intermediate spin state.…”
Section: Introductionmentioning
confidence: 99%